Host and non-host roots in rice: cellular and molecular approaches reveal differential responses to arbuscular mycorrhizal fungi - Fiorilli, Valentina; Vallino, Marta; Biselli, Chiara; Faccio, Antonella; Bagnaresi, Paolo; Bonfante, Paola (Frontiers in Plant Science, 2015)
Oryza sativa, a model plant for Arbuscular Mycorrhizal (AM) symbiosis, has both host and non-host roots. Large lateral (LLR) and fine lateral (FLR) roots display opposite responses: LLR support AM colonization, but FLR do not. Our research aimed to study the molecular, morphological and physiological aspects related to the non-host behavior of FLR. RNA-seq analysis revealed that LLR and FLR displayed divergent expression profiles, including changes in many metabolic pathways. Compared with LLR, FLR showed down-regulation of genes instrumental for AM establishment and gibberellin signaling, and a higher expression of nutrient transporters. Consistent with the transcriptomic data, FLR had higher phosphorus content. Light and electron microscopy demonstrated that, surprisingly, in the Selenio cultivar, FLR have a two-layered cortex, which is theoretically compatible with AM colonization. According to RNA-seq, a gibberellin inhibitor treatment increased anticlinal divisions leading to a higher number of cortex cells in FLR. We propose that some of the differentially regulated genes that lead to the anatomical and physiological properties of the two root types also function as genetic factors regulating fungal colonization. The rice root apparatus offers a unique tool to study AM symbiosis, allowing direct comparisons of host and non-host roots in the same individual plant.